POLA INTERAKSI GURU PAI DALAM PEMBELAJARAN DI MTS. MU’ALLIMIN MUHAMMADIYAH ALABIO KABUPATEN HULU SUNGAI UTARA - Nurhayati Nurhayati (Cross-border, 2021)
The focus of this research is the pattern of PAI teacher interaction in learning at MTs. Mu'allimin Muhammadiyah Alabio, Hulu Sungai Utara Regency. The subject in this study was one PAI teacher at MTs. Mu'allimin Muhammadiyah Alabio, Hulu Sungai Utara Regency. While the object of this research is the pattern of PAI teacher interaction in learning at MTs. Mu'allimin Muhammadiyah Alabio, Hulu Sungai Utara Regency. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique uses qualitative and provides conclusions using general methods based on data in the field. The results of this study indicate that the pattern of PAI teacher interaction in learning at MTs. Mu'allimin Muhammadiyah Alabio, Hulu Sungai Utara Regency, includes 1) One-way interaction patterns have been applied in the learning process by PAI teachers. In the one-way interaction, the PAI teacher explained the material for Islamic religious education using the lecture method and the story method. 2) Two-way interaction patterns have been applied in the learning process by PAI teachers. In the two-way interaction, the PAI teacher really explained the Islamic religious education material using the question and answer method. 3) The pattern of multi-directional interaction has been applied in the learning process by PAI teachers. In this multi-way interaction, the PAI teacher really explained the material for Islamic religious education using the discussion method and group method, as well as the question and answer method.